Metabolism of Phenolic Compounds and Antioxidant Activity in Different Tissue Parts of Post-Harvest Chive (Allium schoenoprasum L.) - Xiaomei Dai; Chonglei Jia; Jiaqi Lu; Zhifang Yu (MDPI AG, 2024)
Chive (Allium schoenoprasum L.) has a strong antioxidant property as it contains abundant phenolic compounds and ascorbic acid. In the present study, we investigated the metabolism of phenolic compounds and the change in antioxidant activity in different tissue parts of post-harvest chives. The results showed that compared with the bottom white part (BW), the round green part (RG) exhibited significantly higher contents of phenolic compounds, increased enzyme activities and enhanced antioxidant activities, indicating that phenolic compounds were mainly synthesised in RG. The expression levels of genes such as phenylalanine ammonia-lyase, cinnamate 4-hydroxylase and 4-coumaroyl-CoA ligase and their corresponding enzyme activities rapidly decreased in RG, whereas they were maintained in BW, suggesting that senescence occurred more rapidly in RG than in BW. Our study provides a theoretical basis for further research into and development of different parts of Allium plants and offers a basis for consumers' nutritional considerations.